The Long-Run Dynamics of Green Technology, Ecological Footprint, and Health Vulnerability in Developed and Developing Countries - Amjad, Muhammad Asif; Rehman, Hafeez ur; Asghar, Nabila (iRASD Journal of Economics, 2023)
Human activities have contributed to environmental degradation for decades, and ecological footprint is considered an effective tool for measuring natural resource consumption. The present study explores the moderating role of green technology to determine the impact of the ecological footprint on the health vulnerability of developed and developing countries from 1990 to 2020. The long-run results are estimated by using the Panel Quantile Regression model at lower, middle, and higher health vulnerability groups. The empirical results show a U-shaped relationship exists between ecological footprint and health vulnerability in all groups. The green technology is used as the moderator term, which shifts the turning point of the U-shaped curve at higher quantile groups of developed countries and middle quantile groups at middle quantiles. Which shows that green technology moderates health vulnerability by reducing the ecological footprint. Furthermore, this study shows that most developing countries fall in the lower health vulnerability group while most developed countries fall in the middle health vulnerability group. This study recommends that these selected countries' governments increase green technologies, reducing the ecological footprint and improving the health sector.